Analisis Pengaruh Penggunaan Media Sosial Tiktok Terhadap Pola Jaringan Komunikasi - Tegar Putra Firmansyah; Rizqillah Duta Saputra; M. Bagas Adi Saputra; Rio Kurniawan (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of TikTok usage on the communication network patterns among Communication Science students of the 2022 cohort at Universitas Trunojoyo Madura. The evolution of social media has shaped new ways of interaction, yet a gap remains in understanding the specific communication network structures that emerge, particularly within an academic setting. Employing a quantitative approach with Social Network Analysis (SNA), data were collected via online questionnaires from 25 students and processed using UCINET software to measure actor centrality. The results of degree centrality analysis identified 'Linda' as the most central actor (opinion leader) with the highest indegree and outdegree scores (6.000). Closeness centrality analysis revealed 'Alfa' as the most efficient information disseminator (content disseminator) with the highest Out-Closeness score (0.453), while 'Bagas', 'Haffyan', and 'Putra' emerged as easily accessible information hubs (trend validators) with high In-Closeness scores. Furthermore, betweenness centrality analysis established 'Alfa' as the most crucial information broker (gatekeeper) with a score of 70.526, connecting various subgroups within the network. This study concludes that TikTok usage fosters a centralized and uneven communication network structure, where a few key actors hold strategic roles as opinion leaders, information disseminators, and brokers who control the flow of communication within the group.